Recent Strategies for the Diagnosis of Early Lyme Disease. (October 2018) - Chou, Eunice; Lin, Yi-Pin; Cady, Nathaniel C.
Lyme disease (LD) is the most common tick-borne disease in the Northern Hemisphere. As the most prevalent vector-borne disease in the USA, LD affects 300, 000 human cases each year. LD is caused by inoculation of the bacterial spirochete, Borrelia burgdorferi sensu lato, from an infected tick. If not treated quickly and completely, the bacteria disseminate from the tick's biting site into multiple organs including the joints, heart, and brain. Thus, the best outcome from medical intervention can be expected with early detection and treatment with antibiotics, prior to multi-organ dissemination. In the absence of a characteristic rash, LD is diagnosed using serological testing involving enzyme-linked immunosorbent assay (ELISA) followed by western blotting, which is collectively known as the two-tier algorithm. These assays detect host antibodies against the bacteria, but are hampered by low sensitivity, which can miss early LD cases. This review discusses the application of some current assays for diagnosing LD clinically, thus providing a foundation for exploring newer techniques being developed in the laboratory for more sensitive detection of early LD.